Robotic Rigor: Validity of the Kinarm End-Point Robot Visually Guided Reaching Test in Multiple Sclerosis - Nick W. Bray, PhD; Syed Z. Raza, MSc; Joselyn Romero Avila, BME(c); Caitlin J Newell, BSc, BA; Michelle Ploughman, PhD (Archives of Rehabilitation Research and Clinical Translation)
Objective: To determine whether robotic metrics: (1) correlate with the Nine-Hole Peg Test (9HPT; good convergent validity); and (2) differentiate between those self-reporting “some hand problems” versus “no hand problems” (good criterion validity). Design: Cross-sectional validation analyses. Setting: Rehabilitation research laboratory located within a hospital. Participants: People with multiple sclerosis self-reporting “some” (n=21; mean age, 52.52±10.69 y; females, n=16; disease duration, 18.81±10.38 y) versus “no” (n=21; age, 51.24±12.73 y; females, n=14; disease duration, 17.71±10.16 y) hand problems. Main Outcome Measures: We assessed hand function using the criterion standard 9HPT and robotic testing. Robotic outcomes included an overall task score, as well as 2 movement planning (ie, reaction time and initial direction angle) and 2 movement correction (ie, movement time and path length ratio) spatiotemporal values. We identified participants reporting “some” versus “no” hand problems via the Multiple Sclerosis Impact Scale-29. We analyzed our nonparametric data using a Mann–Whitney U test and Spearman rank-order correlation. Results: Those reporting “some hand problems” included more right-handed individuals (P=.038); otherwise, the 2 groups were characteristically similar. Visually guided reaching task score and movement planning but not movement correction spatiotemporal values demonstrated moderate correlations with 9HPT for both the dominant (reaction time: r=0.489, P=.001; initial direction angle: r=0.429, P=.005) and nondominant (reaction time: r=0.521, P<.001; initial direction angle: r=0.321, P=.038) side. Further, reaction time, but not 9HPT or any other robotic outcome, differentiated between the 2 groups (P=.036); those reporting “no hand problems” moved faster (ie, dominant side: 0.2810 [0.2605-0.3215] vs 0.3400 [0.2735-0.3725] s). Conclusions: Robotic test metrics demonstrated modest criterion and convergent validity in multiple sclerosis, with reaction time being the most compelling. When looking beyond the task score, spatiotemporal robotic measures may help discern subtle multiple sclerosis-related hand problems. Movement planning spatiotemporal values appear more meaningful than movement correction and could prove fruitful as the target for future intervention strategies.